Analysis of Training and Human Resource Development to Improve the Performance ff Employees of Mitra Medika Pontianak Hospital - Desiana Dian Malasari (Syntax Idea)
Mitra Medika Pontianak Hospital is a public hospital with private ownership under the auspices of PT. Hexa Daya Medika. The purpose of this study is to find out how the Analysis of Training and Human Resource Development to Improve the Performance of Employees of Mitra Medika Pontianak Hospital. The method in this study is the descriptive method. Data collection methods with interview guidelines, and note sheets. The population in this study was all employees of Mitra Medika Hospital Pontianak. The data analysis used is qualitative analysis. The results of this study are very important medical and non-medical training is carried out to realize excellent and quality service in hospitals. Training and development must be carried out regularly by the hospital. So that every health worker who works in the hospital can work professionally, according to professional standards, hospital service standards, applicable operational standards, professional ethics, respect patient rights and prioritize patient safety